1996
DOI: 10.1295/polymj.28.594
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study on the Dissolved State of Polyacrylonitrile in Various Solvents

Abstract: ABSTRACT:An attempt was made to elucidate the dissolved state of polyacrylonitrile (PAN) in various solvents by analyzing 13 C NMR chemical shift difference for the arbitrarily chosen two NMR peaks derived from PAN molecules and by considering solvent effect on the electro-magnetical parameters introduced previously with aid of solvation phenomena of PAN in solvents. For this purpose, R-PAN andy-PAN employed hithetofore were subject to the analysis. Solvents employed included typical organic solvents such as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Due to the interaction of solvent to polymer is dependent on polymer stereoregularity and the solvent power is related to the solvent ability to interact on the long meso (m) sequence part in PAN, 18 the lower isotactic CO 2 -PAN means that it has good dissolve ability in solvent, which is proved by being dissolved in DMF easily for wet-spinning, the mentioned work was appeared in our another research paper. 8 …”
Section: Analysis Of Polymerization Mechanism Through Sequence Distrimentioning
confidence: 99%
“…Due to the interaction of solvent to polymer is dependent on polymer stereoregularity and the solvent power is related to the solvent ability to interact on the long meso (m) sequence part in PAN, 18 the lower isotactic CO 2 -PAN means that it has good dissolve ability in solvent, which is proved by being dissolved in DMF easily for wet-spinning, the mentioned work was appeared in our another research paper. 8 …”
Section: Analysis Of Polymerization Mechanism Through Sequence Distrimentioning
confidence: 99%
“…The solvents in which PAN can be dissolved are polar solvents such as dimethylformamide (DMF) [12], dimethyl sulfoxide (DMSO) [13], dimethylacetamide (DMAc) [14], dimethyl sulfone, tetramethyl sulfide, and aqueous solutions of ethylene carbonate and some mineral salts [15,16]. This makes PAN very useful for a wide range of different applications [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The type of solvents lead to different interactions with PAN chains that affect the rheological properties of PAN solutions. Hattori et al . studied the dissolution status of PAN in various solvents by NMR and found that the solvent–PAN interactions also depended on the PAN stereoregularity.…”
Section: Introductionmentioning
confidence: 99%